Associations of Circulating Lymphocyte Subpopulations with Type 2 Diabetes: Cross-Sectional Results from the Multi-Ethnic Study of Atherosclerosis (MESA). - Nels C Olson; Margaret F Doyle; Ian H de Boer; Sally A Huber; Nancy Swords Jenny; Richard A Kronmal; Bruce M Psaty; Russell P Tracy (PLoS ONE)
Objective Distinct lymphocyte subpopulations have been implicated in the regulation of glucose homeostasis and obesity-associated inflammation in mouse models of insulin resistance. Information on the relationships of lymphocyte subpopulations with type 2 diabetes remain limited in human population-based cohort studies. Methods Circulating levels of innate (γδ T, natural killer (NK)) and adaptive immune (CD4+ naive, CD4+ memory, Th1, and Th2) lymphocyte subpopulations were measured by flow cytometry in the peripheral blood of 929 free-living participants of the Multi-Ethnic Study of Atherosclerosis (MESA). Cross-sectional relationships of lymphocyte subpopulations with type 2 diabetes (n = 154) and fasting glucose and insulin concentrations were evaluated by generalized linear models. Results Each standard deviation (SD) higher CD4+ memory cells was associated with a 21% higher odds of type 2 diabetes (95% CI: 1-47%) and each SD higher naive cells was associated with a 22% lower odds (95% CI: 4-36%) (adjusted for age, gender, race/ethnicity, and BMI). Among participants not using diabetes medication, higher memory and lower naive CD4+ cells were associated with higher fasting glucose concentrations (p<0.05, adjusted for age, sex, and race/ethnicity). There were no associations of γδ T, NK, Th1, or Th2 cells with type 2 diabetes, glucose, or insulin. Conclusions A higher degree of chronic adaptive immune activation, reflected by higher memory and lower naive CD4+ cells, was positively associated with type 2 diabetes. These results are consistent with a role of chronic immune activation and exhaustion augmenting chronic inflammatory diseases, and support the importance of prospective studies evaluating adaptive immune activation and type 2 diabetes.